Grammotology of Yeld - Maralbek Е. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2022)
The article analyzes the works on the Kazakh writing of the outstanding figure of the Alash movement of the early twentieth century, a scientist, talented linguist, and one of the founders of Kazakh linguistics Eldes Omaruly. The articles of the scientist on the complex problems of the Kazakh spelling of the 20-30s of the twentieth century are collected in detail. The author analyzed conclusions on the most relevant topics of Kazakh writing in detail, such as the principles of writing, the ratio of oral speech and writing, writing letters, writing roots and affixes, writing of words, spelled together and separately, the connection of intonation and stress with writing, the spelling of onomastic names, the spelling of terms. Also, the scientific continuity of Eldes Omaruly and his teacher Akhmet Baitursynov on the topic of spelling is considered, his original research is compared with that of his teacher, his contribution to the development of Kazakh spelling, concrete evidence of spelling rules associated with his name. As a result of the analysis, scientific evidence will be presented from the works of scientists on the problematic issues of Kazakh spelling that have arisen due to the current reform of the alphabet.